Carbon dots enhance the recovery of microalgae bioresources from wastewater containing amoxicillin. (September 2021) - Zhao, Zhenhao; Xue, Ren; Fu, Liang; Chen, Congli; Ndayisenga, Fabrice; Zhou, Dandan
Graphical abstract: Highlights: CDs promoted the recovery of microalgae bioresources from toxic wastewater. Chlorella specific growth rates increased by 36.0% (day 8–13) and 52.7% (day 14–18). AMO removal increased by 18.6%, and the toxicity of products was eliminated. Nitrogen and phosphorous removal increased by 14.6% and 9.9%, respectively. Pigments, proteins and lipids increased by 16.6%, 24.8% and 19.5%, respectively. Abstract: The cultivation of microalgae using wastewater could bring some major economic benefits; however, the toxics in wastewater typically lead to a reduction in bioresource production. In this study, carbon dots (CDs) could enhance the photosynthetic activity of Chlorella under antibiotic stress because they might optimize photoluminescence by red-shifting incident light. Adding of 1 mg/L CDs increased the specific growth rate of Chlorella by 36.0% (day 8–13) and 52.7% (day 14–18) and significantly increased photosystems II activity. This treatment also increased amoxicillin removal by 18.6%. Thus, the toxicity of residuals was significantly eliminated (P < 0.05). The removal of nitrogen and phosphorous was increased by 14.6% and 9.9%, respectively. The production of pigments, lipids and proteins was increased by 16.6%, 19.5% and 24.8%, respectively. This work provided a new strategy of using CDs to mediate the coupling of microalgal bioresources production and toxic wastewater purification.